Evaluating the Efficacy of Electrical Vestibular Stimulation (VeNS) on Insomnia Adults: Study Protocol of a Double-Blinded, Randomized, Sham-Controlled Trial - Cheung, Teris; Lam, Joyce Yuen Ting; Fong, Kwan Hin; Cheng, Calvin Pak-Wing; Ho, Alex; Sittlington, Julie; Xiang, Yu-Tao; Li, Tim Man Ho (International journal of environmental research and public health, 2023)
Insomnia is a common health problem in the general population. There are different ways to improve sleeping habits and quality of sleep; however, there is no clinical trial using transdermal neurostimulation to treat individuals with symptoms of insomnia in Asia. This gives us the impetus to execute the first study in Asia which aims to evaluate the efficacy of Electrical Vestibular Stimulation (VeNS) on individuals with insomnia in Hong Kong. This study proposes a two-armed, double-blinded, randomized, sham-controlled trial including the active VeNS and sham VeNS group. Both groups will be measured at baseline (T1), immediately after the intervention (T2), and at the 1-month (T3) and 3-month follow-up (T4). A total of 60 community-dwelling adults aged 18 to 60 years, with insomnia symptoms will be recruited in this study. All subjects will be computer randomized into either the active VeNS group or the sham VeNS group on a 1:1 ratio. All subjects in each group will receive twenty 30-min VeNS sessions during weekdays, which will be completed in a 4-week period. Baseline measurements and post-VeNS evaluation of the psychological outcomes (i.e., insomnia severity, sleep quality and quality of life) will also be conducted on all participants. The 1-month and 3-month follow-up period will be used to assess the short-and long-term sustainability of the VeNS intervention. For statistical analysis, a mixed model will be used to analyze the repeated measures data. Missing data will be managed by multiple imputations. The level of significance will be set to p < 0.05. Significance of the study: The results of this study will be used to determine whether this VeNS device can be considered as a self-help technological device to reduce the severity of insomnia in the community setting. We registered this clinical trial with the Clinical trial government, identifier: NCT04452981.